The analysis of convergence process of voivodships' efficiency in Poland using the DEA metod - Dariusz Wozniak; Piotr Czarnecki; Robert Szarota (European Regional Science Association (ERSA), 2011)
Since 1999 - when the new administrative division in Poland was introduced - it has been possible to measure and compare standard of living between Polish and other European regions (NUTS II). In 2004 Poland has joined the European Union. Since that year voivodships have become main beneficiaries of the EU funds. The essential part of that aid is related to the EU cohesion policy (convergence objective). According to the fifth cohesion report "cohesion policy has made a significant contribution to spreading growth and prosperity across the Union, while reducing economic, social and territorial disparities". However, the differences in standard of living still remains significant between countries as well as between regions within one country. In many researches the level of welfare is measured using "classic" indicators (GDP per capita, GNI per capita, unemployment rate, etc.). In this paper the authors focus on the regional economies' efficiency. The efficiency will be measured using the Data Envelopment Analysis. Due to the method used, the efficiency will be measured as relative in nature, i.e. will be compared between voivodships within the period of research. The goal of the paper is to analyze variety of relative voivodships' efficiency in order to answer the question if the dispersion in efficiency is increasing or decreasing over time.
Keywords: 330